P1-S2.50 Anal non-L Chlamydia trachomatis infection in men who have sex with men, at l'Actuel, Montreal, Quebec. (10th July 2011) - Charest, L; Thomas, R; Trottier, B; Boissonnault, M; Legault, D; Longpré, D; Szabo, J; Maziade, P J; Machouf, N
Abstract : Few cases of sexually transmitted Hepatitis C infection (HCV) in men who have sex with men (MSM) had been reported in the literature. Background: The incidence of genital infection from non-L Chlamydia trachomatis (CT) is increasing in the province of Quebec. Traditionally it was more prevalent in young women. In the last few years, CT infection has emerged in men who have sex with men (MSM) group. The objective of this study was to describe anal non-L CT infection in MSM in an HIV-STI clinic in a large urban setting. Methods: Retrospective study of anal non-L CT cases diagnosed at Clinique l'Actuel in 2010. We collected information on age at diagnosis, HIV status, CT serovars, symptoms, mode of transmission and concomitant presence of CT in urine. An anal swab specimen was collected with a TAAN test (BD Probe Tec TM). Results: From 2006 to 2009, we diagnosed respectively 42, 58, 82 and 118 anal non-L CT infection in MSM. In 2010, we diagnosed 154 different anal non-L CT infections in 152 MSM. Patient's age at diagnosis was 33 years (IQR—25−38) from 18 to 70 years. 28% were HIV+ at time of diagnosis. Anal infection was primarily caused by serovars J (35%), G (31%), D (23%), E (10%), F (1%) and C (1%). Among HIV patients the serovars was predominantly J (46%), D (30%) and G (24%). But this difference was not statistically significant. Anal non-L CT infection was detected in asymptomatic patients while screening in 54% of case. 7% of MSM had no symptom but consulted because they were notified by a sexual partner. 39% had symptoms—proctitis (26%), urethritis (11%) or symptom of other STI including syphilis and HIV primary infection (2%). Mode of transmission for the anal infection was not specifically specified in the file of the patients, but 88% reported anal unprotected penetration in the past year, 12 % did not report anal penetration but had mouth to anus contact (rimming) or friction from penis to anus. One patient reports sharing anal toys. Urine CT was positive in 18% of MSM, so those MSM had two infected sites. Conclusion: Given the high rate of positive results, MSM should be screen with a TAAN test for anal CT infection. This screening should be included in the regular follow-up of HIV patients. MSM community should be aware of this emerging infection. Public health authority should focus on developing and promoting new guidelines of screening, access to validated test with identification of serovars.